Aplikasi Mindahan New Normal Sebagai Panduan Adaptasi Kebiasaan Baru - Abdur Rouf; Rina Yulianti (Jurnal Ilmiah Pangabdhi, 2021)
The world began to be attacked by a new outbreak of Covid-19 that can infect people quickly, infect the respiratory tract and cause fatalities. To learn and improve knowledge about Covid-19 can be done through mobile devices. This research aims to create an application as a new normal guide to encounter the Covid-19 pandemic for the community, especially Mindahan Village. This application was developed with java programming language by utilizing android studio. The results of this study are Mindahan New Normal application based on android as a new normal guide with self-check feature, Covid-19 response webview, and emergency service contactsKey Words : automatic disinfectant booth, Covid-19, droplet, contagion, infected, viruses.